Effect of increasing dietary isoacid levels on total tract and apparent ileal nutrient digestibility and fermentation products in growing pigs fed corn-soybean meal diets - Angie P. Benavides-Infante; Lucas A. Rodrigues; Mike T. Socha; Wesley P. Schweer; Crystal L. Levesque; Jorge Y. Perez-Palencia (Journal of Animal Science and Biotechnology)
Abstract Background Isoacids are the product of branched-chain amino acid fermentation and are naturally produced in the hindgut by microbial fermentation. In ruminants, supplementation of isoacids as a feed additive improves fiber utilization, with a positive impact on animal productivity. However, information on how isoacids impact nutrient digestibility in swine is limited. The objective of this experiment was to determine the optimal inclusion level of an isoacid blend product based on apparent ileal digestibility (AID) and apparent total tract digestibility (ATTD) of nutrients and fermentation products in the ileal digesta and feces of growing pigs fed a corn-soybean meal diet. Methods Twelve ileal cannulated pigs (20.9 ± 0.6 kg) were used in a 5-period crossover design with 6 diets and 2 replicate pigs in each period. Dietary treatments consisted of increasing levels (0%, 0.5%, 0.75%, 1%, 1.25%, and 1.5%) of an isoacid blend (isobutyrate, isovalerate, and 2-methyl butyrate, 1:1:1) added to a corn-soybean meal basal diet. Each experimental period consisted of 14 d: 10 d for acclimatization to the diets, 2 d for fecal collection, and 2 d for digesta collection. Results Isoacids supplementation quadratically improved the AID of hemicellulose (P < 0.05) and tended to improve the AID of crude fiber (P < 0.1). The AID of most indispensable amino acids (except Met + Cys, Trp, and Val) as well as the ATTD of crude protein, gross energy, neutral detergent fiber, and hemicellulose improved or tended to improve linear or quadratically (P < 0.05 or P < 0.1). In addition, the ATTD values of Arg, His, Ile, Leu, Met + Cys, Phe, Thr, and Val increased quadratically (P < 0.05). Collectively, 1% of isoacids inclusion resulted in the greatest response. Furthermore, isoacids supplementation tended to increase (P = 0.071, quadratically) the concentration of ammonia and decreased (P < 0.05) the concentrations of acetic acid and total volatile fatty acids with a tendency to decrease (P = 0.064) isovaleric acid in the ileal digesta. In fecal samples, the proportion of acetic acid decreased (P < 0.05) quadratically, whereas the proportions of propionic, valeric, and caproic acids tended to increase linearly and/or quadratically (P < 0.1). Conclusions Isoacids supplementation at 1% in swine diets can improve nutrient digestibility, particularly amino acids and fiber at the ileal level and ATTD of crude protein, gross energy, and hemicellulose.